Modulating the electronic properties of Ag/Au implanted 2D chalcogenide layer on polymers - Miksova, Romana; Ceccio, Giovanni; Novák, Josef; Macková, Anna (HNPS Advances in Nuclear Physics, 2025)
The unique properties enable molybdenum disulfide (MoS2) exhibit great potential applications in the fields of electronic and optoelectronic devices. MoS2 is a typical two-dimensional (2D) layered material shows low band gap. MoS2 was developed on polyethylene terephthalate (PET) substrate for the construction of flexible devices with Ion beam sputtering (IBS). These MoS2/PET composites were enriched with Ag and Au using ion beam implantation with energy up to 1.8 MeV and ion fluences in the range of 5×1014 to 5×1015 cm-2. The implantation energy was chosen according to the SRIM simulation program to achieve the required depth for both ion species. Thickness of the MoS2 layer as well as Ag and Au depth profiles were examined using Rutherford backscattering method (RBS). Surface morphology before and after ion beam implantation was checked using Scanning electron microscopy (SEM). The electrical properties of prepared structures were characterized by 2-point configuration. Ion implantation has been shown to decrease sheet resistance.